Трансформації релігійного мистецтва в епоху Ренесансу - Головей, В. Ю.; Golovey, V. Y. (Східноєвропейський національний університет імені Лесі Українки, 2013)
У статті висвітлено трансформації релігійного мистецтва в епоху Ренесансу; проаналізовано сутнісні змі-ни в характері художньої репрезентації священного в контексті секуляризації культури. Доведено, що струк-турно-смислові метаморфози мистецтва органічно пов’язані зі структурними трансформаціями соціокультур-ного процесу. The article examines the essential changes in the artistic representation of the sacred. The process of forming a new paradigm in the understanding of art’s representative nature and the essential factors of artistic and cultural metamorphosis under the influence of the secularization have been studied. Revealed that shift in emphasis from the transcendent to the immanent level, from theocentrism to anthropocentrism, from symbolism to realism caused the transformation of the icons to the picture and lead to the formation of a new concept of the art image. Religious images fingered the function of the illustratively and rhetorical images, simultaneously the distance for the profane measurement has been disappeared. It is proved that formal and semantic metamorphoses of art have been organically linked with the structural transformations of the socio-cultural process.
The Transformation of Religious art in the Renaissance
Keywords: релігійне мистецтво; the religious art; сакральне; the sacred; Ренесанс; the Renaissance; секуляризація; secularization; суб’єктивізація; subjectification